2014
DOI: 10.2508/chikusan.85.301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ear-corn silage on milk production and volatile compounds of milk in lactating cows

Abstract: Corresponding : Yasuko UEDA (fax : +81 (0) 11-859-2178, e-mail : okabeys@affrc.go.jp) Two feeding trials were carried out to investigate the effects of ensiled ear-corn harvested by selfpropelled forage harvester on DM intake, milk production and composition, and volatile compounds of milk compared with imported flaked corn for lactating cows. A 3 × 3Latin square study was conducted with 6 Holstein cows each trial. Dietary treatments were flaked corn (FC), flaked corn and ear-corn silage (MIX), and ear-corn si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Keen (1998) showed that a European-type diet consisting largely of concentrates (with both starch and fatty acid precursors, i.e., grain, meals, among others) promoted the formation of γ-lactone precursors in the rumen. In addition, Ueda et al (2014) reported that milk from cows fed corn silage had a high content of lactones. Thus, it seems that the amount of concentrate or corn silage in the feed affects the content of lactones in the milk.…”
Section: Distinguishing Between Feeding Systems Using Volatile Organimentioning
confidence: 99%
“…Keen (1998) showed that a European-type diet consisting largely of concentrates (with both starch and fatty acid precursors, i.e., grain, meals, among others) promoted the formation of γ-lactone precursors in the rumen. In addition, Ueda et al (2014) reported that milk from cows fed corn silage had a high content of lactones. Thus, it seems that the amount of concentrate or corn silage in the feed affects the content of lactones in the milk.…”
Section: Distinguishing Between Feeding Systems Using Volatile Organimentioning
confidence: 99%
“…Milk composition parameters including milk fat, milk protein, lactose, and solids not fat content also changed with seasonal progress (p < .01) but did not differ between the ECS and non-ECS farms. In a study comparing the supply of ECS and flaked dry corn for lactating cows fed silage-based diets (Tada et al, 2018;Ueda et al, 2014), there was no difference in milk yield or milk composition.…”
Section: Milk Productionmentioning
confidence: 99%
“…Among these type of feed, the production of ear corn silage (ECS) has been growing in prevalence within TMR centers and contractor organizations in Hokkaido, since ECS has high nutritive value and fermentation qualities (Oshita, Nemoto, Aoki, Ueda, & Aoki, 2016; Otsu et al., 2012). Milk production from cows fed with ECS supplement in silage‐based feeding was equal to that from cows fed with a flaked dry corn supplement (Aoki, Oshita, Ueda, Nemoto, & Aoki, 2016; Tada, Aoki, & Oshita, 2018; Ueda et al., 2014).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations